2007
DOI: 10.1210/jc.2007-0173
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Polymorphism at the Interferon-Induced Helicase (IFIH1) Locus Contributes to Graves’ Disease Susceptibility

Abstract: We confirm a significant contribution of the Ala946Thr IFIH1 polymorphism to organ-specific autoimmune diseases, extending the range of conditions associated with this variant to include Graves' disease. This polymorphism may also contribute to several other autoimmune disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 19 publications
7
77
0
4
Order By: Relevance
“…The IFIH1 gene has been implicated as a susceptibility gene in other autoimmune diseases, such as type I diabetes 17 or Graves' disease. 18 Common genetic variants have been implicated in various autoimmune diseases or in families with several cases affected by different diseases. 19,20 It is of interest to note that the IFIH1-GCA-KCNH7 locus was not a region of interest in a recent first genome-wide association scan in MS.…”
Section: Discussionmentioning
confidence: 99%
“…The IFIH1 gene has been implicated as a susceptibility gene in other autoimmune diseases, such as type I diabetes 17 or Graves' disease. 18 Common genetic variants have been implicated in various autoimmune diseases or in families with several cases affected by different diseases. 19,20 It is of interest to note that the IFIH1-GCA-KCNH7 locus was not a region of interest in a recent first genome-wide association scan in MS.…”
Section: Discussionmentioning
confidence: 99%
“…The effect found for MS was of similar magnitude to the one originally described regarding T1D 3 and also present in Graves' disease. 8 Strong linkage disequilibrium within this locus precluded us from further dissecting where the etiologic gene resides. The polymorphism rs1990760 in the IFIH1 gene was proposed as the causal variant based on the conservation of aligned sequences in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…7 More recently, association of this locus with Grave's disease was also found. 8 We aimed at identifying whether this chromosomal region was a common susceptibility locus for other autoimmune disease as MS.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some studies have shown strong associations between the rs1990760 polymorphism of the IFIH1 gene and other autoimmune diseases, such as psoriasis (63,64), chronic periodontitis (63), polymyositis (65), multiple sclerosis (57,66), systemic lupus erythematosus (67), and Graves' disease (68).…”
Section: Associations Between Ifih1 and Other Autoimmune Conditionsmentioning
confidence: 99%